Genotype, B‐vitamin status, and androgens affect spaceflight‐induced ophthalmic changes. Issue 1 (27th August 2015) - Zwart, Sara R.; Gregory, Jesse F.; Zeisel, Steven H.; Gibson, Charles R.; Mader, Thomas H.; Kinchen, Jason M.; Ueland, Per M.; Ploutz‐Snyder, Robert; Heer, Martina A.; Smith, Scott M.
ABSTRACT: Ophthalmic changes have occurred in a subset of astronauts on International Space Station missions. Visual deterioration is considered the greatest human health risk of spaceflight. Affected astronauts exhibit higher concentrations of 1‐carbon metabolites ( e.g., homocysteine) before flight. We hypothesized that genetic variations in 1‐carbon metabolism genes contribute to susceptibility to ophthalmic changes in astronauts. We investigated 5 polymorphisms in the methionine synthase reductase (MTRR), methylenetetrahydro folate reductase (MTHFR), serine hydroxymethyltransferase (SHMT), and cystathionine β‐synthase (CBS) genes and their association with ophthalmic changes after flight in 49 astronauts. The number of G alleles of MTRR 66 and C alleles of SHMT1 1420 both contributed to the odds of visual disturbances. Preflight dehydroepiandrosterone was positively associated with cotton wool spots, and serum testosterone response during flight was associated with refractive change. Block regression showed that B‐vitamin status and genetics were significant predictors of many of the ophthalmic outcomes that we observed. In one example, genetics trended toward improving ( P = 0.10) and B‐vitamin status significantly improved ( P < 0.001) the predictive model for refractive change after flight. We document an association between MTRR 66 and SHMT1 1420 polymorphisms and spaceflight‐induced vision changes. This line of research could lead to therapeutic options for both space travelers and terrestrial patients.—Zwart, S. R., Gregory, J. F., Zeisel, S. H., Gibson, C. R., Mader, T. H., Kinchen, J. M., Ueland, P. M., Ploutz‐Snyder, R., Heer, M. A., Smith, S. M. Genotype, B‐vitamin status, and androgens affect spaceflight‐induced ophthalmic changes. FASEB J. 30, 141‐148 (2016). www.fasebj.org